(untitled) (Вісник: Міжнародні відносини, 2025)
Abstract. The article considers the problems of modern international organizations and obsolescence of the world order - multipolarity. The author analyzes the dynamics of the development of global institutions that manage international processes, in particular the United Nations. Modern challenges and shortcomings of existing global institutions that manage international processes are analyzed, in particular the issues of legitimacy, efficiency and ability to adapt to new geopolitical realities. Special attention is paid to the need to create a new international organization that would better meet the requirements of the modern ultrapolar world and ensure more effective and fair management of global processes. A new concept of an international organization is proposed, which should solve the issues of international security, economic development, environmental stability and protection of human rights in a more balanced and inclusive manner. The article provides recommendations on the main principles and mechanisms of functioning of such an organization, which would contribute to stability and prosperity on a global scale.